Reflections on the peace process in Andhra Pradesh - Kannabiran, Kalpana; Kannabiran, Vasanth; Volga (2005)
Initiating a peace process with the Naxalites was not an act of benevolence by the Congress government, but the first step towards fulfilling a commitment on the basis of which it was given a mandate by the people. It is now time to address several questions pertaining to the entire process that spanned eight months, including the role of the media, the bearing of arms in public, the issue of land reforms and that of `neutrality' in political matters. The ultimate undoing of a laboriously crafted process of democratisation by a newly elected government is cause for serious concern. - Reproduced.
Keywords: Terrorism